Impact of bystander-focused public health interventions on cardiopulmonary resuscitation and survival: a cohort study - Audrey L Blewer, PhD; Andrew Fu Wah Ho, MBBS; Nur Shahidah, BA; Alexander Elgin White, MPH; Pin Pin Pek, MPH; Yih Yng Ng, MBBS; Desmond Renhao Mao, MBBS; Ling Tiah, MBBS; Michael Yih-Chong Chia, MBBS; Benjamin Sieu-Hon Leong, MBBS; Si Oon Cheah, MBBS; Lai Peng Tham, MBBS; et al. (Elsevier, 2020)
Summary: Background: Bystander cardiopulmonary resuscitation (CPR) increases an individual's chance of survival from out-of-hospital cardiac arrest (OHCA), but the frequency of bystander CPR is low in many communities. We aimed to assess the cumulative effect of CPR-targeted public health interventions in Singapore, which were incrementally introduced between 2012 and 2016. Methods: We did a secondary analysis of a prospective cohort study of adult, non-traumatic OHCAs, through the Singapore registry. National interventions introduced during this time included emergency services interventions, as well as dispatch-assisted CPR (introduced on July 1, 2012), a training programme for CPR and automated external defibrillators (April 1, 2014), and a first responder mobile application (myResponder; April 17, 2015). Using multilevel mixed-effects logistic regression, we modelled the likelihood of receiving bystander CPR with the increasing number of interventions, accounting for year as a random effect. Findings: The Singapore registry contained 11 465 OHCA events between Jan 1, 2011, and Dec 31, 2016. Paediatric arrests, arrests witnessed by emergency medical services, and healthcare-facility arrests were excluded, and 6788 events were analysed. Bystander CPR was administered in 3248 (48%) of 6788 events. Compared with no intervention, likelihood of bystander CPR was not significantly altered by the addition of emergency medical services interventions (odds ratio [OR] 1·33 [95% CI 0·98-1·79]; p=0·065), but increased with implementation of dispatch-assisted CPR (3·72 [2·84-4·88]; p<0·0001), with addition of the CPR and automated external defibrillator training programme (6·16 [4·66-8·14]; p<0·0001), and with addition of the myResponder application (7·66 [5·85-10·03]; p<0·0001). Survival to hospital discharge increased after the addition of all interventions, compared with no intervention (OR 3·10 [95% CI 1·53-6·26]; p<0·0001). Interpretation: National bystander-focused public health interventions were associated with an increased likelihood of bystander CPR, and an increased survival to hospital discharge. Understanding the combined impact of public health interventions might improve strategies to increase the likelihood of bystander CPR, and inform targeted initiatives to improve survival from OHCA. Funding: National Medical Research Council, Clinician Scientist Award, Singapore and Ministry of Health, Health Services Research Grant, Singapore.